LEADERSHIP FACTORS AS PREDICTORS OF CREATIVITY BEHAVIOR FOR CITY IMAGE: A STUDY IN BANDUNG CITY, INDONESIA - Juanim, Juanim (Faculty of Economic and Business, University of Pasundan, 2025)
This research is conducted as a continuation of previous research and is part of a broader investigation into leadership and city image. Previous studies have demonstrated that leadership has an impact on the image of a city through community commitment. Community commitment, in turn, can enhance the image of Bandung as a creative city. Therefore, this study examines the factors of transformational leadership that promote creative behavior in society, thereby strengthening Bandung's image as a creative city. The study involved a sample of 222 individuals who completed 250 questionnaires. The data were analyzed using SEM Lisrel. The results indicate that creative behavior can positively influence the image of Bandung city. Additionally, leaders must inspire the community to embrace creativity. The research implications and recommendations for future studies are discussed in the following section.